Examining Asghar Ali Engineer’s Qur’anic Interpretation of Women in Islam - Nuryatno, M. Agus (Al-Jami'ah: Journal of Islamic Studies, 2007)
This article discusses Asghar Ali Engineer’s interpretation of women in Islam. Two topics discussed in this article are the status of women in Islam and the veil. Engineer offers an approach in understanding the Qur’an to deal with these topics and his method is based on three principles: firstly, the Qur’an has two ingredients: normative and contextual. Normative ingredient refers to the fundamental values and principles of Qur’an such as equality and justice, and these principles are eternal and can be applied in various social contexts. Contextual revelations, on the other hand, deal with verses that were tailored to socio-historical problems of the time. In line with the changes in context and time these verses can be abrogated. Secondly, the interpretation of the Quranic verses is very dependent on one’s own perceptions, world-view, experiences and the sociocultural background in which he/she lives. Thus, a ‘pure’ interpretation of the Scripture is not possible; it is always influenced by sociological circumstances, no one can be free of such influences. Thirdly, the meaning of the Quranic verses unfolds with times, therefore, the interpretations of classical scholars can be radically different from the interpretation of modern scholars. This is because Quranic verses often use symbolic or metaphorical language that is ambiguous in meaning. This ambiguity serves, of course, to promote flexibility and creative change. These three principles can be employed to understand the status of women in Islam and the veil.